2021
DOI: 10.2478/aut-2019-0074
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Dyeing Performance and Antibacterial Activity of Silver Nanoparticle-Immobilized Cotton Woven Fabric

Abstract: The purposes of the current research were to deposit the silver nanoparticles on the surface of a textile woven fabric and evaluate their dyeing performance and antibacterial activity. The synthesis of silver nanoparticle (Ag°) is done by the in situ method. Strong alkali is used to improve functionality of cellulose before the application of silver nitrate salt (AgNO3). The silver nanoparticle is formed by reduction of ascorbic acid. Various instrumental analyses are done to prove the formation of nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Figure 3 (a) shows the untreated fabric where no Ag nanoparticle exists. It can be noted that this method shows more deposition of Ag nanoparticles than that of other in-situ deposition methods of our previous work [12,22]. By initial observation, SEM image proves the successful immobilization of Ag nanoparticles into the cotton fabric surface.…”
Section: Characterization Of Fabricmentioning
confidence: 58%
See 1 more Smart Citation
“…Figure 3 (a) shows the untreated fabric where no Ag nanoparticle exists. It can be noted that this method shows more deposition of Ag nanoparticles than that of other in-situ deposition methods of our previous work [12,22]. By initial observation, SEM image proves the successful immobilization of Ag nanoparticles into the cotton fabric surface.…”
Section: Characterization Of Fabricmentioning
confidence: 58%
“…The reason behind the improvement of dyeing performance is the mordanting power of Ag nanoparticles that ensures to grip more dyestuffs on fabric surface that causing increased color depth. Our previous work also revealed the improvement of color performance of cotton fabric where Ag nano was deposited by in-situ method on alkali pre-modi ed fabric [22]. Since all color performance increases, this treatment has also a positive in uence on the dyeing performance of the cotton fabric.…”
Section: Dyeing Performancementioning
confidence: 85%
“…The tendencies of the two curves in the figure appear to be genuinely homogeneous, largely denoting the characteristic peaks of the major functional groups of the cellulosic structure of cotton fabrics. It can be observed that the main functional groups of the cellulosic structure include the peaks at 3323-3334 cm −1 , 2913-2947 cm −1 , 1141-11,667 cm −1 , and 1017-1044 cm −1 [23,24,41]. According to the IR table, the peaks at 3329 cm It is apparent that no substantial modification happened on cotton because of caustic soda (NaOH) or silver treatment, which is consistent with the findings of Li Shuhui et al [42].…”
Section: Atr-ftir Spectra Of Agnp-deposited Samplesmentioning
confidence: 99%
“…Graphene oxide, 32 lignin molecules, 33 and NP-impregnated textiles/fabrics 29 , 34 have been studied for their antibacterial and antiviral characteristics; however, most of these investigations have focused on ex situ coating of NPs on textiles utilizing pre-prepared liquids containing the NPs and/or physical deposition techniques. 29 , 32 , 33 It is also worth noting that graphene has been linked to cancer.…”
Section: Introductionmentioning
confidence: 99%
“…31 Antimicrobial coatings, according to the same study, could provide an extra layer of protection, limiting the spread of coronaviruses in indoor spaces and public locations where contamination is constant. Graphene oxide, 32 lignin molecules, 33 and NP-impregnated textiles/fabrics 29,34 have been studied for their antibacterial and antiviral characteristics; however, most of these investigations have focused on ex situ coating of NPs on textiles utilizing pre-prepared liquids containing the NPs and/or physical deposition techniques. 29,32,33 It is also worth noting that graphene has been linked to cancer.…”
Section: ■ Introductionmentioning
confidence: 99%